Prevalence of hypertension and its risk factors among school teachers in Dhaka, Bangladesh - Barua, Ripon; Alam, Monzurul; Parvin, Nadira; Chowdhury, Rajib (International Journal of Research in Medical Sciences, 2018)
Background: School teachers in urban area are experiencing sedentary life style behaviors. This study was aimed to determine the prevalence and risk factors of hypertension (HTN) among school teachers in Dhaka city. Methods: This cross-sectional study was carried out from May to October of 2017. Total 323 school teachers in Dhaka city aged between 25-59 years were enrolled using cluster random sampling technique. Data on socio-demographic profile, different risk factors, co-morbidities, family history and blood pressure (BP) were recorded. HTN was recorded according to pre-defined criteria. Factors associated with HTN analyzed by Chi-square test (χ2). Results: The prevalence of HTN among school teachers was 52%. The mean ± SD age was 46.5±7.8 years. Majority teachers (52%) were earning between 20,000 and 50,000 Bangladeshi Taka per month and about 61.6% had service duration >15 years. Development of HTN was significantly associated with age, monthly family income and service duration (p=0.001). Majority participants were female (65.6%) and female to male ratio was 1.9:1. Female teachers were more hypertensive compared to male (68% vs 32%). Taking extra salt (OR 1.977, 95% CI 1.269-3.079), low intake of fresh vegetables (OR 2.048, 95% CI 1.228-3.416), higher waist circumference (OR 1.990, 95% CI 1.006-3.933) and mental distress (OR 1.724, 95% CI 1.045-2.844) were found to be significantly associated with HTN. Conclusions:The prevalence of HTN was higher among the study participants. Building awareness by promoting healthy life style and behaviors for prevention and control of HTN should be given importance among teachers.